DISCRETION OF LAW ENFORCEMENT OFFICIALS IN HANDLING CHILDREN WHO COMMIT CRIMES: A STUDY OF COMPLIANCE WITH THE PRINCIPLES OF RESTORATIVE JUSTICE - Lubis, Muhammad Ansori (Jurnal Ilmiah METADATA, 2025)
The discretionary power of law enforcement officials in handling juvenile delinquency cases represents a critical juncture where legal formalism intersects with restorative justice principles. This study examines the extent to which law enforcement discretion aligns with restorative justice frameworks when processing children in conflict with the law. Utilizing a qualitative approach with case study methodology, this research analyzes 45 cases of juvenile delinquency handled by law enforcement agencies across three jurisdictions over a two-year period (2022-2024). Data were collected through in-depth interviews with 30 law enforcement officials, legal practitioners, and juvenile justice stakeholders, supplemented by document analysis of case files and policy documents. The findings reveal significant variations in discretionary practices, with compliance rates to restorative justice principles ranging from 42% to 78% across jurisdictions. Key factors influencing discretionary decisions include organizational culture, training exposure to restorative justice approaches, severity of offenses, victim-offender dynamics, and institutional support mechanisms. The study identifies four discretionary typologies: formalistic enforcers, contextual mediators, welfare-oriented facilitators, and hybrid practitioners. While formal policies endorse restorative approaches, implementation gaps persist due to insufficient training, limited resources, ambiguous procedural guidelines, and resistance to paradigm shifts from retributive to restorative models. The research contributes to juvenile justice literature by mapping the discretionary landscape and its alignment with restorative justice imperatives, offering evidence-based recommendations for policy reform, capacity building, and institutional strengthening to enhance child-centered justice delivery systems.